FACTORS CAUSING WORK ACCIDENTS AT THE MEDAN CLASS A SEARCH AND RESPECT AGENCY OFFICE - Irfansyah, Ahmad; Afiqah, Viona; Hasibuan, Desi Fitriah; Pratiwi, Adisti Eka; Hatasya, Khairunisa Deri; Purba, Monica Amelia; Salsabillah, Tasya; Ningsih, Nurafrillia; Ansah, Rendi; Azmy, Puan Arliza (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2024)
Work accidents are unplanned events that cause injuries, pain, or damage that occur at work. Work accidents usually occur in workplaces that have high potential hazards. This study aims to determine the potential dangers that allow accidents, accidents that often occur, and the causes of accidents that often occur. Research Types and Design Using Qualitative Descriptive Methods With a Case Study Approach. In this study, the focus of the study contains the main subjects: unsafety action, age, use of PPE, K3 Knowledge, UNSAFE Conditions, and Ergonomics. From the results of the situation analysis that has been carried out and observations obtained at the Medan Class A Search and Relief Office, it is known that several factors cause work accidents. In the theory of three main factors (three main factors theory), 3 factors cause work accidents, namely human factors, environmental factors, and ergonomic factors.